2014
DOI: 10.1002/aur.1426
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of Emotion Regulation Measurement in Individuals With Autism Spectrum Disorder

Abstract: Emotion regulation (ER) difficulties are a potential common factor underlying the presentation of multiple emotional and behavioral problems in individuals with Autism Spectrum Disorder (ASD). To provide an overview of how ER has been studied in individuals with ASD, we conducted a systematic review of the past 20 years of ER research in the ASD population, using established keywords from the most comprehensive ER literature review of the typically developing population to date. Out of an initial sampling of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 144 publications
(138 reference statements)
1
54
0
Order By: Relevance
“…Weiss, Thomson, and Chan (2014) recently conducted a systematic literature review of emotion regulation measurement in individuals with autism spectrum disorder, and identified several measures of naturalistic observation of emotion regulation; for example, Jahromi, Meek, and Ober-Reynolds (2012) conducted a study in which coders coded for 12 emotion regulation strategies in 10-second intervals. Results indicated that children with autism employed more avoidance and venting strategies when faced with frustration.…”
Section: Emotion Regulation As a New Rdoc Domainmentioning
confidence: 99%
“…Weiss, Thomson, and Chan (2014) recently conducted a systematic literature review of emotion regulation measurement in individuals with autism spectrum disorder, and identified several measures of naturalistic observation of emotion regulation; for example, Jahromi, Meek, and Ober-Reynolds (2012) conducted a study in which coders coded for 12 emotion regulation strategies in 10-second intervals. Results indicated that children with autism employed more avoidance and venting strategies when faced with frustration.…”
Section: Emotion Regulation As a New Rdoc Domainmentioning
confidence: 99%
“…Additionally, ER is important not only for understanding associated features of ASD, but is relevant to core symptoms of social communication that define ASD as well (Mazefsky et al, 2013; Weiss, Thomson, & Chan, 2014). For example, emotional awareness, recognition of emotional experience in others, and impaired identification and expression of social gestures may all reflect impaired modulation of social-emotional information processing (Bachevalier & Loveland, 2006; Lecavalier, 2006; Zwaigenbaum et al, 2005) because they require the adjustment of internal affective experiences to changing environmental conditions (Gross, 2013; Ochsner, Bunge, Gross, & Gabrieli, 2002; Ray, Wilhelm, & Gross, 2008).…”
mentioning
confidence: 99%
“…In addition, all children had an IQ above 79, and it is unclear how the current findings might differ for school-age children with more severe ASD symptomatology or lower intellectual functioning. This study also could have benefited from using multiple measures of child emotion regulation (e.g., parent report, behavioral observation, psychophysical measurement; Weiss et al 2014) instead of relying solely on coding child report of emotion regulation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of emotion regulation in children with ASD found that research has largely relied on self-report (38%) or informant report (44%); fewer used naturalistic observation/behavior coding (31%) or open-ended measures (13%); and only two (6%) of the studies explored correlates of emotion regulation (Weiss et al 2014). Self-report in children with ASD may be problematic due to the lack of correspondence with parent report (Mazefsky et al 2011; Meyer et al 2006; White et al 2009) and with physiological measures (Shalom et al 2006), raising the question of the validity of self-report responses in this population.…”
Section: Introductionmentioning
confidence: 99%